Digital Transformation In Business Operations To Support The Country's Economy - Dwi Angreni Rumatamerik; Nurul Asfiah (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Social Enterprises (SE) are responsible for social and environmental issues. As a hybrid organization that combines the business and volunteer sectors, SE becomes an important tool in analyzing organizational settings and developing plans to achieve social goals. In this article it is emphasized that understanding business models is very important. The social business model (SEMC) and Business Model Canvas (BMC) are useful tools to help SEs create strategies that are responsive to the challenges they face. BMC uses a multidimensional approach to mission values ​​and objectives, as well as a deep understanding of stakeholders, to become a powerful tool for driving progress and generating sustainable positive impact. Over time, social entrepreneurs will have to incorporate new principles into their practices. Our results also show that these sustainable and gradual techniques not only change value, but also influence the development of companies and the surrounding society. Therefore, this technique not only helps maintain the existing structure, but also helps make necessary changes. Finally, our research advances our understanding of social entrepreneurship and provides social enterprises seeking greater social change with practical insight.